2012
DOI: 10.1016/j.amjsurg.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal fluid: a potential mechanism of systemic neutrophil priming in experimental intra-abdominal sepsis

Abstract: Background Recent studies suggest that peritoneal fluid (PF) may be an important mediator of inflammation. We hypothesize that PF may drive systemic inflammation in intra-abdominal sepsis by representing a priming agent for neutrophils. Methods PF was collected 12 hours after initiation of intra-abdominal sepsis in swine. Naïve human neutrophils were primed with PF prior to treatment with N-formyl-met-leu-phe or phorbol 12-myristate 13-acetate to elucidate receptor dependent and independent mechanisms of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“… 17 22 These mediators are released into peritoneal fluid before being taken up into mesenteric lymph and plasma. 21 , 23 Cytokine-rich mesenteric lymph primes neutrophils and may induce distant organ injury. 24 , 25 As such, several animal and human studies have reported that peritoneal and systemic proinflammatory cytokine concentrations after abdominal injury or intra-abdominal sepsis differentiate between survivors and nonsurvivors of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 17 22 These mediators are released into peritoneal fluid before being taken up into mesenteric lymph and plasma. 21 , 23 Cytokine-rich mesenteric lymph primes neutrophils and may induce distant organ injury. 24 , 25 As such, several animal and human studies have reported that peritoneal and systemic proinflammatory cytokine concentrations after abdominal injury or intra-abdominal sepsis differentiate between survivors and nonsurvivors of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of all immune cells are localised in the gastrointestinal tract, attributing the gut as a cytokine-generating organ [14,15] and an important mediator of inflammation [16], the so-called brain that drives the immune response. Pathophysiological mechanisms associated with the inflammatory response are leading to capillary leakage, IAH and development of multiple organ failure [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, inflammatory fluid is retained in the gut wall, intestinal villi secrete fluid into the gut lumen, and the luminal fluid does not rapidly regress from the gastrointestinal tract, contributing to IAH and even ACS [14,21]. Animal and human studies show that circulation of lymph containing a high concentration of cytokines can cause severe liver, kidney and lung injury and the development of MODS and is therefore associated with poor outcomes [16,18,20-22]. In animal models, abdominal NPT was shown to prevent the development of lung injury and was associated with decreases in leukocytes migrated to the kidney and liver [16,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary endpoints of interest include trial feasibility (number of patients enrolled/number of eligible candidates) and the differential effects of the allocated TAC dressings on several physiological and organ dysfunction outcomes, including: (1) the plasma concentration of TNF-α and IL-1, -8, -10, and −12 at 24 and 48 h; (2) the collective peritoneal and systemic mediator profiles (see below); (3) the activation potential of peritoneal fluid [70,71]; (4) peritoneal fluid drainage volume; (5) postoperative daily fluid balance; (6) SOFA scores and individual organ system components of these scores; (7) the PaO 2 /FIO 2 ratio; (8) vasopressor requirements and arterial lactate levels; (9) need for renal replacement therapy; (10) RIFLE criteria; (11) APACHE-II scores; and (12) 24 h enteral tolerance (if no gastrointestinal anastomosis was performed).…”
Section: Methodsmentioning
confidence: 99%